(untitled) (Journal of the College of Basic Education, 2023)
This paper aims at measuring the effectiveness of the ( Preparation for TOEFL Test Training programme ) conducted by Staff Development Centre on the participants’ achievement in the post – test at the end of the programme . Two groups have been selected for this purpose (experimental and control group ) containing (15) participants each . The experimental group was taught by using computer assisted instruction in special lecture room provided with LCD screen ( clear sound , clear pictures ) with special TOEFL CDs and books from local market and other designed by the staff of the center to reinforce the learning process . The second group was taught using the traditional method ( cassettes , board ) . The programme for each group lasted ( 4) weeks . The participants in both groups subjected to a post–test which is the same for both using the statistical analysis T-test . The results showed the achievement of experimental group in post–test was much better than the other group . The paper concludes that the teaching methods applications and using modern techniques and various audio – visual aids can highly improve the efficiency of the programme and it also recommends that CDs and computer-assisted language learning should be incorporated into the regular classes, rather than scheduling them separately. The paper came out with some recommendations in this respect .